Essays on development and international economics - Brey, Björn (2021)
My doctoral thesis comprises three chapters focussing on the impact of technology and trade on long-run economic development and political outcomes. The first chapter explores the effect of the early adoption of electricity at the end of the 19th in Switzerland on local economic development in the long-run. The second chapter explores the role of colonial trade on economic and political developments in British India during the 20th century. The third chapter analyses the effect of recent technological change, mainly automation, on the making of immigration policy in the United States since the 1970s.